The Dual Role of Autophagy in Cancer Development and a Therapeutic Strategy for Cancer by Targeting Autophagy - Yun, Chul Won (Int J Mol Sci, 2020)
Autophagy is a delicate intracellular degradation process that occurs due to diverse stressful conditions, including the accumulation of damaged proteins and organelles as well as nutrient deprivation. The mechanism of autophagy is initiated by the creation of autophagosomes, which capture and encapsulate abnormal components. Afterward, autophagosomes assemble with lysosomes to recycle or remove degradative cargo. The regulation of autophagy has bipolar roles in cancer suppression and promotion in diverse cancers. Furthermore, autophagy modulates the features of tumorigenesis, cancer metastasis, cancer stem cells, and drug resistance against anticancer agents. Some autophagy regulators are used to modulate autophagy for anticancer therapy but the dual roles of autophagy limit their application in anticancer therapy, and present as the main reason for therapy failure. In this review, we summarize the mechanisms of autophagy, tumorigenesis, metastasis, cancer stem cells, and resistance against anticancer agents. Finally, we discuss whether targeting autophagy is a promising and effective therapeutic strategy in anticancer therapy.